Locus coeruleus inhibition of vibrissal responses in the trigeminal subnucleus caudalis are reduced in a diabetic mouse model - Mesa-Lombardo, Alberto; García-Magro, Nuria; Nuñez, Angel; Martin, Yasmina B. (Frontiers in Cellular Neuroscience, 2023)
Diabetic neuropathy is a loss of sensory function beginning distally in the lower extremities that is also characterized by pain and substantial morbidity. Furthermore, the locus coeruleus (LC) nucleus has been proposed as playing an important role in descending pain control through the activation of 2-noradrenergic (NA) receptors in the spinal dorsal horn. We studied on control and diabetic mice the effect of electrical stimulation of the LC nucleus on the tactile responses in the caudalis division of the spinal trigeminal nucleus (Sp5C), which is involved in the relay of orofacial nociceptive information. Diabetes was induced in young adult C57BL/6J mice with one intraperitoneal injection of streptozotocin (50 mg/kg) daily for five days. The diabetic animals showed pain in the orofacial area because they had a decrease in the withdrawal threshold to the mechanical stimulation in the vibrissal pad. LC electrical stimulation induced an inhibition of vibrissal responses in the Sp5C neurons when applied at 50 and 100 ms before vibrissal stimulation in the control mice, but inhibition was reduced in the diabetic mice. These effects may be due to a reduction in the tyrosine hydroxylase positive (TH+) fibers in the Sp5C, as was observed in the diabetic mice. LC-evoked inhibition was decreased by an intraperitoneal injection of the antagonist of the 2-NA receptors, yohimbine, indicating that it was due to the activation of α2-NA receptors. The decrease in the LC-evoked inhibition in the diabetic mice was partially recovered when clonidine, a non-selective α2-agonist, was injected intraperitoneally. These findings suggest that in diabetes there is a reduction in the NA inputs from the LC in the Sp5C that may favor the development of chronic pain.